Anti-inflammatory Activity and Antioxidant Potential of Aqueous Extracts from Stem Bark of Geoffroea decorticans - Jofré, Mariana (2017)
In the present work we investigated, for the first time, the anti-inflammatory activity and the antioxidant properties ofaqueous and ethanolic extracts, obtained from stem bark of Geoffroea decorticans (Gill. ex Hook. et Arn.) Burk. (Fabaceae). G.decorticans, commonly known as ?chañar? or ?chañarcillo?, is a traditional argentinean plant used as emollient, balsamic, antitussive,expectorant and anti-inflammatory. The stem bark was collected from San Francisco del Monte de Oro, San Luis, Argentina.Anti-inflammatory activity was evaluated by carrageenan-induced paw edema in rats. Antioxidant activity was tested using1,1-Diphenyl-2-picrylhydrazyl radical-scavenging activity (DPPH), 2,2´-Azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) radicalscavenging activity (ABTS) and ferric ion-reducing power (RP-Fe) assays. Aqueous extract 10% p/v showed anti-inflammatory activity (3h, 48% inhibition, 5h 37% inhibition and 7h 17% inhibition) and antioxidant activity (DPPH, IC50 (mg/mL) = 0.098 ± 0.032; ABTS, IC50 (mg/mL) = 0.022 ± 0.343, RP-Fe IC50 (mg/mL) = 1.124 ± 0.146). In the other hand, the ethanolic extract 5% p/v, presented anti-inflammatory activity (3h, 34% inhibition, 5h 38% inhibition and 7h 35% inhibition) and antioxidant activity (DPPH, IC50 (mg/mL) = 0.133 ± 0.027; ABTS, IC50 (mg/mL) = 0.086 ± 0.262, RP-Fe IC50 (mg/mL) = 7.089 ± 0.104). These results suggest that, also fruits, the aqueous and ethanolic extracts from the stem bark of G. decorticans present significant anti-inflammatory activity and antioxidant properties.